The Influencing Factors of China's Electricity Consumption Based on Structural Decomposition Analysis - Fengtao GUANG; Yongxiu HE; Peipei YOU; Xiao GAO (Zhongguo dianli)
Since the economic development has stepped into a new normal phase in China, the average annual growth rate of its electricity consumption has slowed down, which shows the deviation from the rate of economic growth. Based on the input-output analysis for electrical energy, structural decomposition analysis is carried out to evaluate the driving factors for the changes of use in relation to electricity consumption. By comparing the effects of various factors among different economic stages and analyzing the growth patterns of electricity consumption, we aim to investigate the reasons for the slowing annual growth rate of electricity consumption. Results show that: per capita final demand level has always been the major driving factor of the growth in electricity consumption, but its proportion of contribution has a decreasing tendency. Except for the period of 2010—2012, direct electricity consumption coefficients have always the primary factor which causes the decrease of electricity consumption, but the final demand structure promotes the growth of electricity consumption with a relatively smaller pulling rate. The engine of electricity consumption growth shifted from export-driven in 2005—2007 to investment-driven in 2007—2010 and consumption-driven in 2010—2015.